A Conceptual Forecasting Analysis of International Trade Aspects Based on Globalization Impact Issues - Kontsas, Stamatis; Kalogiannidis, Stavros (International Journal of Scientific Research and Management (IJSRM), 2022)
Global GDP is really important for trade, since the larger the global economy, the more goods and services available for trade. Global GDP grew by around two-thirds in real terms between 2000 and 2020 – or 2.6% per year on average.2020 saw some of the largest trade reductions and output volumes for both industrial production and goods trade since WWII. The year 2020 was marked by some of the largest reductions in trade and output volumes since WWII. The declines in both world industrial production and goods trade in the first half of 2020 were of similar depth to those at the trough of the Global Financial Crisis (GFC). In addition, trade and production impacts across specific goods, services and trade partners were highly varied.Initial pandemic-era expectations for a double-digit decline in world merchandise trade in 2020 did not materialise. Global trade turned out to recover from the shock at an extraordinarily fast pace from around mid-2020.